The Battle Behind the Wire U.S. Prisoner and Detainee Operations from World War II to Iraq - Benard, Cheryl (RAND Corporation, 2011)
This report finds parallels in U.S. prisoner and detainee operations in World War II, Korea, Vietnam, and Iraq: underestimation of the number to be held, hasty scrambling for resources, and inadequate doctrine and policy. Later, attempts to educate and influence prisoners and detainees are often made. The authors recommend that detailed doctrine should be in place prior to detention and that detainees should be interviewed when first detained.